Chemo mechanical caries removal CMCR; efficacy of Carisolv gel in primary molar teeth - Pervez, Jazib; Hafiz Muhammad Adil; Mehmood Rana (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate the efficacy of CariSolv gel with respect to chemo-mechanical caries removal in primary molar teeth. Method: The cross-sectional study was conducted at the Department of Paediatric Dentistry, Bakhtawar Amin Dental College and Hospital, Multan, Pakistan, from July to December 2022, and comprised patients of either gender aged 6-12 years having vital, primary molar teeth with clinical and radiographic evidence of carious lesion. Freshly prepared CariSolv gel 0.2ml to 1.0ml was applied to carious dentine for a minimum of 30 seconds, using chemo-mechanical caries removal hand instruments. The cavity preparation was rinsed and dried. Image caries detector dye was applied by micro brush for 10 seconds. After the cavity preparation was washed and dried, any red-stained dentine indicated residual infected dentine. A maximum of 3 chemo-mechanical caries removal cycles were allowed. Data was analysed using SPSS 26.0. Results: Of the 134 patients, 74(55.2%) were boys and 60(44.8%) were girls. The overall mean age was 8.55+1.58 years. The procedure was successful in 115(85.8%) cases. Age and gender were not significantly associated with the outcome (p>0.05). Conclusions: Chemo-mechanical caries removal method using CariSolv gel was found to be a viable alternative to traditional drilling techniques for caries removal in primary molar teeth. Key Words: Caries, CariSolv, Paediatric dentistry, Primary molar teeth, Restorative dentistry.